Side specific effect of 5-hydroxytryptamine on NaCl transport in the apical and basolateral membrane of rat tracheal epithelia - Nam, Byung Do; Park, Hee Ju (Physiological research, 2006)
5-Hydroxytryptamine (5-HT) can be released from mast cells and platelets through an IgE-dependent mechanism and may play a role in the pathogenesis of allergic bronchoconstriction. However, the effect of 5-HT on ion transport by the airway epithelium is still controversial. The objective of this study was to determine whether 5-hydroxytryptamine (5-HT) regulates NaCl transport by different mechanisms in the apical and basolateral membrane of tracheal epithelia. We studied the rat tracheal epithelium under short-circuit conditions in vitro. Short-circuit current (I(sc)) was measured in rat tracheal epithelial monolayers cultured on porous filters. 5-HT inhibited Na(+) absorption [measured via Na(+) short-circuit current (I(Na)(sc))] in the apical membrane and stimulated Cl(-) secretion [measured via Cl(-) short-circuit current (I(Cl)(sc))] in the basolateral membrane. Functional localization using selective 5-HT agonists and antagonists suggest that I(Cl)(sc)is stimulated by the basolateral membrane-resident 5-HT receptors, whereas I(Na)(sc) is inhibited by the apical membrane-resident 5-HT2 receptors. The basolateral addition of 5-HT increases intracellular cAMP content, but its apical addition does not. The addition of BAPTA/AM blocked the decrease of I(Na)(sc)which was induced by the apical addition of 5-HT, and 5-HT increased intracellular Ca concentrations. These results indicate that 5-HT differentially affects I(Na)(sc)and I(Cl)(sc)across rat tracheal monolayers through interactions with distinct receptors in the apical and the basolateral membrane. These effects may result in an increase of water movement towards the airway lumen.
Keywords: signální transdukce; Signal Transduction; AMP cyklický; Electrophysiology; Trachea; Serotonin; serotonin; Respiratory Mucosa; chlorid sodný; Cell Polarity; krysa rodu Rattus; epitelové buňky; elektrofyziologie; Receptors, Serotonin; zvířata; Cells, Cultured; Cyclic AMP; polarita buněk; potkani Sprague-Dawley; Epithelial Cells; Serotonin Agents; trachea; kultivované buňky; respirační sliznice; Rats; receptory serotoninové; Rats, Sprague-Dawley; Animals; Sodium Chloride; Membrane Potentials; membránové potenciály; serotoninové látky